الحافظ أبو نُعيم الأصبهاني (ت:430ه) وكتابه "تاريخ أصبهان": دراسة وصفية: Al-Hafiz Abu Nu'aim al-Asbahani (d. 430 AH) and his book "Tarikh Asbahan": A descriptive study - Zubair Ahmad bin Asadillah (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2026)
This research aims to introduce Abu Nu'aym al-Isfahani and conduct a descriptive study of his book, "The History of Isfahan." The research employed both inductive and descriptive methodologies. It concluded that Abu Nu'aym was the Imam, the memorizer of hadith, Ahmad ibn Abdullah ibn Ahmad ibn Ishaq ibn Musa ibn Mihran al-Mihrani, known as Abu Nu'aym. There is some disagreement regarding the exact date of his birth. He traveled to various regions in pursuit of knowledge, studying under numerous prominent hadith scholars and experts in the field. Subsequently, a large number of hadith scholars studied under him, directly hearing from him and transmitting his narrations and writings. His works encompassed a wide range of subjects, including hadith sciences, biographies, history, asceticism, spiritual refinement, and creed. Initially a Sufi, he later renounced his former beliefs and died adhering to the Salafist creed. His book, *Tarikh Isfahan* (History of Isfahan), contains a wealth of texts with their chains of transmission, as well as a vast amount of scholarly material compiling the history of Isfahan. It is distinguished by the abundance of sources that drew upon and quoted from this book. These quotations demonstrate the author's high standing in the field of biographical evaluation (ilm al-rijal), particularly concerning the scholars of Isfahan. There are points of agreement and points of disagreement between Abu al-Shaykh al-Isfahani's Tabaqat al-Muhaddithin bi-Isfahan wa-al-Waridin 'alayha (Biographical Dictionary of Hadith Scholars in Isfahan and Those Who Came to It) and Abu Nu'aym al-Isfahani's Tarikh Isfahan.